Interfacing C328 CMOS camera with an ATMega32L microcontroller - Kayastha, Shrijandra Nath (Journal of Science and Engineering, 2012)
A small low power VGA camera module C328 can perform as a JPEG compressed still camera and can be attached to a microcontroller, PC, wireless or PDA host, etc. This paper introduces the C328 CMOS camera interface with a low power CMOS 8 bit ATMega32L microcontroller based on AVR enhanced RISC architecture. The ATMega32L executes powerful instruction in single clock cycle and achieves throughputs approaching 1MIPS per MHz that allows designing the system with optimum power consumption versus processing speed. The camera module C328 was serially interfaced with microcontroller, and the lowest resolution JPEG image (80x64) compression mode was made for the analysis of packet of image data in hex format. It was specifically designed for the cost effective embedded vision system that can be used in robot, security, monitoring etc.